PENGARUH KEMAMPUAN KOGNITIF DAN PENGHARGAAN TERHADAP KINERJA GURU LEMBAGA BIMBINGAN DAN KONSULTASI BELAJAR NURUL FIKRI DI JAKARTA - Intan, rani (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2015)
The objective of this research is to study the effect of cognitive ability and reward on job performance of teachers in Nurul Fikri institution. This research was conducted at the Nurul Fikri institution as the non-formal education (out-of school institution) in Jakarta. The method used to analyze this research is the causal study. The sample of this research were 66 teachers that were selected randomly. From this research results were found that; (1) there is a direct effect of cognitive ability on job performance; (2) there is a direct effect of reward on job performance; and (3) there is a direct effect of cognitive ability on reward. According to the findings, it could be concluded that job performance of the teachers were effected by cognitive ability and reward. And cognitive ability is the most dominant effect to improve job performance of the teachers. In the other words, we can say that the higher cognitive ability will improve the reward received and the quality of job performance. Finally it’s concluded that cognitive ability and reward should be considered in improving job performance of the teachers